2015
DOI: 10.1111/ijcp.12741
|View full text |Cite
|
Sign up to set email alerts
|

Older type 2 diabetic patients are more likely to achieve glycaemic and cardiovascular risk factors targets than younger patients: analysis of a primary care database

Abstract: SummaryBackgroundOlder subjects with type 2 diabetes mellitus (T2DM) have differential characteristics compared with middle‐aged or younger populations, and require tailored management of the disease.AimsTo evaluate how clinical characteristics, degree of control of glycaemia and cardiovascular risk factors, presence of chronic complications and treatments differ between older T2DM patients and younger adults.MethodsCross‐sectional study using data from a population‐based electronic database. We retrieved data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 26 publications
11
31
0
1
Order By: Relevance
“…In this group, HDL-c levels were lower than those of individuals with glycaemia under 100 mg/dL. Both groups presented BMI above normal values supporting the connection between obesity, DM and CVD as showed by other authors [17] [18]. Alterations in the lipid profile of DM patients are common in the literature, although with inconsistent findings when comparing the different fractions and components.…”
Section: Discussionsupporting
confidence: 77%
“…In this group, HDL-c levels were lower than those of individuals with glycaemia under 100 mg/dL. Both groups presented BMI above normal values supporting the connection between obesity, DM and CVD as showed by other authors [17] [18]. Alterations in the lipid profile of DM patients are common in the literature, although with inconsistent findings when comparing the different fractions and components.…”
Section: Discussionsupporting
confidence: 77%
“…A great number of treatment options show notable efficacy in RCTs, but their impact on glycaemic control in real-world clinical practice is usually less than expected. 27 Our results 23,24 Our results also suggest that the best glycaemic control is achieved in the elderly and in patients with comorbid conditions, whereas the worst control was observed among women.…”
Section: Discussionsupporting
confidence: 60%
“…The earlier study on trajectories also reported that poor responders were represented by a relatively younger population . These findings are supported by other studies showing that patients at younger ages have poorer glycaemic control . One of the causes for this could be that younger patients may have a more irregular lifestyle and consequently more problems in adhering to treatment with insulin .…”
Section: Discussionsupporting
confidence: 54%